Chemical composition, antioxidant and antibacterial activities of extracts obtained from the roots bark of Arbutus andrachne L. a Lebanese tree. - Emna Abidi; Jean Habib; Touhami Mahjoub; Feten Belhadj; Meriem Garrab; Assem Elkak (International Journal of Phytomedicine, 2016)
Context and purpose of the study: The leaves, fruits, barks and roots of Arbutus andrachne L (A. andrachne), have been adopted to have high therapeutic value resulting from the presence of antioxidant compounds such as flavonoids, phenolic and tannins. In the present work, three extracts obtained from A. andrachne roots bark were evaluated for their antioxidant and antibacterial activities .The total phenolic content, flavonoid, condensed tannins and anthocyanins were determined in order to correlate them with the antioxidant activity of extracts. Main findings: The highest amounts of phenolic and tannins were found in the ethyl-acetate, while the anthocyanins ones were highly observed in the methanol-water extract. The lowest IC50 values for DPPH (0.6 µg/mL), and metal chelating assay (13.45µg/mL) were recorded in the ethyl-acetate extract and the methanolic one respetively. Gram positive bacteria (S. aureus and E. faecalis) were more susceptible to the antimicrobial potential of the methanol extract, while E.coli and P. aeruginosa as Gram negative bacteria turned out to be more resistant to the same extract. The ethyl-acetate extract was more effective on E. faecalis than on S. aureus; while E. coli and P. aeruginosa were the most resistant to this extract. Brief summary and potential implications: An appropriate dose of antioxidants derived from A. andrachne bark of the roots extracts in the human diet can help to avoid the risk of contracting diseases where ROS are involved in the pathogenesis. In fact, phenolic compounds in these extracts are among the natural antioxidants being studied by the scientific community due to their biological properties, e.g., antioxidant and antimicrobial activities.